Alaska oil reserves : hearing before the Committee on Energy and Natural Resources, United States Senate, One Hundred Fourth Congress, first session, on oil production at Prudhoe Bay, Alaska, July 18, 1995. - United States. Congress. Senate. Committee on Energy and Natural Resources. (Washington : U.S. G.P.O. : For sale by the U.S. G.P.O., Supt. of Docs., Congressional Sales Office, 1995)
Mode of access: Internet.